Trabalho calado : os Kaingang do Toldo Chimbangue e as indústrias de carne - Stefanuto, Míriam Rebeca Rodeguero (2017)
This dissertation examines the relationship between work in the slaughterhouses and the Kaingang way of life in the Toldo Chimbangue indigenous land, located in the municipality of Chapecó, in the western region of the state of Santa Catarina. The region is an important producer of pork and poultry meat, and the state is one of the most important of the meat sector in Brazil, producing for the domestic and foreign markets. Recently, the Kaingang have been hired by the slaughterhouses, that it’s offers transportation from the village to the industries. As this research seeks to present, being employed in slaughterhouses means subjecting to conditions that are admittedly exhaustive and harmful to workers. In addition to health issues, a repetitive production line that gets sick the Kaingangs bodies differs from village practices and knowledge, especially those concerning animal breeding, feeding, notions of work and the territory of the Toldo Chimbangue. These elements are what constitute and characterize the Kaingang being, according to themselves, and the work in the slaughterhouses and what it represents and implies is opposed to this way of life considered truly Kaingang. It is on those relationships and oppositions that this research is concerned.